A secreted C-type lectin in Periplaneta americana functioning in antibacterial activity, innate immune signaling and leg regeneration - Liu, Xiaoxuan; Sun, Nan; Geng, Shuang; Xian, Shuqi; Wu, Xiaojuan; Huang, Ying; Pei, Yechun (Frontiers in Immunology, 2026)
IntroductionC-type lectins are important pattern-recognition receptors that play essential roles in innate immune responses by recognizing pathogen-associated molecular patterns. However, their biological functions in Periplaneta americana have not been systematically investigated.MethodsTwo PaSCLec isoforms predicted by RNA-seq, designated PaSCL-Ad and PaSCL-Reg, were identified using Rapid Amplification of cDNA Ends (RACE) and Nanopore sequencing. Tissue-specific expression and inducible expression following bacterial challenge were analyzed. Recombinant PaSCL-Ad and PaSCL-Reg proteins were produced to examine their binding activities to microbial polysaccharides, bacterial agglutination, antimicrobial effects, and membrane-disruptive activity. Hemocyte phagocytosis was evaluated by immunocytochemical analysis. RNA interference was employed to assess the role of PaSCLec in immune regulation and leg regeneration, followed by transcriptional analyses.Results and DiscussionTotal PaSCLec (PaSCL-Ad and PaSCL-Reg) was most highly expressed in the hemolymph and was significantly upregulated after challenge with Escherichia coli and Staphylococcus aureus. Both recombinant proteins bound lipopolysaccharides, peptidoglycan, mannan, and β-glucan in a dose-dependent manner, and agglutinated Gram-positive (Staphylococcus aureus, Bacillus subtilis) and Gram-negative (Escherichia coli, Salmonella Typhimurium) bacteria in a Ca2+-dependent manner. rPaSCL-Ad inhibited the growth of all tested bacteria and potentially compromised the membrane integrity of E. coli in a Ca2+-independent manner. Both recombinant proteins enhanced hemocyte phagocytic activity by promoting bacteria–hemocyte interactions. Knockdown of PaSCLec reduced the expression of multiple antimicrobial peptides and transcription factors associated with the Toll, IMD, and JAK/STAT signaling pathways; these effects were partially rescued by recombinant protein supplementation. In addition, PaSCLec knockdown impaired leg regeneration. qRT-PCR suggested an association between PaSCLec activity and JAK/STAT-related genes during regeneration. These findings demonstrate that PaSCLec is a multifunctional secreted lectin involved in microbial recognition, immune effector regulation, and leg regeneration in P. americana, although the underlying molecular mechanisms require further investigation.